Effects of GnRH Agonist and Dienogest in Combination on HE4 and CA125 Levels in Patients with Adenomyosis and Adenomyoma: A Prospective Cohort Study - DongGe Wang; LiMei Ji; CenLin Jia; MingJun Shao (IMR Press, 2023)
Background: The traditional pathology of adenomyosis (AM) suggests that this is a common benign uterine disease. Hysterectomy is the gold standard of care and is viewed as a decisive treatment for AM; however, more conservative treatment approaches are required to maintain fertility. Unfortunately, there are few studies focusing on medical treatments for AM. The objective was to investigate the effect of gonadotropin-releasing hormone agonist (GnRH-a) combined with dienogest on serum human epididymis secretory protein 4 (HE4) and carbohydrate antigen 125 (CA125) levels in patients with AM and adenomyoma. Methods: We addressed our objective using a prospective cohort design. We selected 120 patients treated for AM and adenomyoma from February 2019 to April 2021 in our hospital. The patients were divided into a control group and a study group. The control group was treated with GnRH-a alone, while the study group was treated with GnRH-a combined with dienogest. The curative effect, dysmenorrhea score, dysmenorrhea grade, serum CA125 and HE4 levels, size of the uterine lesions, and incidence of adverse reactions were compared between the two groups. Results: When comparing the two groups, the study group consisted of 43 cases that were significantly effective, 12 effective cases, and five ineffective cases, thus, the effective rate was 91.67%. The control group displayed 23 significantly effective cases, 21 effective cases, and 16 ineffective cases, thus the effective rate for the control group was 73.33%. The curative effect in the study group was higher than in the control group, and the difference was statistically significant (p < 0.05). There was no significant difference in the dysmenorrhea score between the two groups before treatment (p > 0.05). However, after treatment, the dysmenorrhea score in the study group was lower than in the control group 1 month, 3 months, and 6 months after treatment (p < 0.05). There was no significant difference in the levels of serum CA125 and HE4 between the two groups before treatment, but the levels of serum CA125 and HE4 decreased after treatment, and the levels of serum CA125 and HE4 in the study group were lower than in the control group. There was no significant difference in the size of the uterine lesions between the two groups before treatment (p > 0.05). After treatment, the size of the uterine lesions in the study group was smaller than in the control group (p < 0.05). There was no statistical difference in the incidence of adverse reactions between the study group and the control group. Conclusions: GnRH-a combined with dienogest was effective treatment than the single GnRH-a treatment in patients with AM and adenomyoma as evidenced by decreased serum CA125 and HE4 levels, menstrual volume, and dysmenorrhea. The combined treatment could more effectively alleviate the clinical symptoms, reduce the focus volume, and improve the treatment efficiency. For patients with larger adenomyomas requiring conservative treatment, GnRH-a combined with dienogest is a promising therapeutic option.